Finite element analysis of unsteady MHD Blasius and Sakiadis flow with radiation and thermal convection using Cattaneo-Christov heat flux model. (24th September 2021) - Ali, Liaqat; Liu, Xiaomin; Ali, Bagh; Abdal, Sohaib; Zulqarnain, Rana Muhammad
Abstract: A theoretical study is performed on the effect of magnetohydrodynamic field, Biot number on classical Blasius and Sakiadis flows of heat transfer characteristics over a sheet by using the Cattaneo-Christov flux model. Many technical processes involving hydromagnetics flows and thermal expansion in the porous medium have been studied in recent years, such as casting, compact heat exchangers, liquid metal filtering, fusion control, and nuclear reactor cooling. A uniform magnetic field acts perpendicular to the sheet, with a source of radiative heat and a convective condition at the boundary. Appropriate similarity transforms have been used to convert the governing nonlinear partial differential equations to their ordinary differential form. Galerkin numerical technique is harnessed to yield a solution that looks into the varying behaviors of the concentrations, flow speed, temperature in the boundary layers, and gradients of these quantities at the boundary due to parametric variation. The effect of governing physical parameters over the velocity, temperature, concentration, skin friction, Nusselt number, and Sherwood number are demonstrated graphically. The utmost pertinent consequences of this study are the enrichment in the strength of magnetic field reduces the velocity flows creating lesser velocity of the boundary layer flow in both the Sakiadis and Blasius. In addition, Biot number, radiation parameter, and thermophoresis parameter made directly increasing impact on the temperature but the opposite effect of thermal relaxation on the temperature profile is observed. The convergence of numerical technique is noticed for optimum meshing and the accuracy of the presented results has been verified with an excellent comparison of present results with previous studies.